1983
DOI: 10.1037/0097-7403.9.3.292
|View full text |Cite
|
Sign up to set email alerts
|

Visual search and selection of natural stimuli in the pigeon: The attention threshold hypothesis.

Abstract: During visual search for samples of varying proportions of familiar, natural food grains displayed against a complex gravel background, pigeons exhibited "matching selection," a tendency to overselect the more common grain. The matchingselection effect was decreased at low levels of stimulus/background contrast and reversed when the grains were highly conspicuous. The results were consistent with the hypothesis that stimulus detectability should be enhanced by recent experience with a particular grain type, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
221
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(237 citation statements)
references
References 32 publications
14
221
2
Order By: Relevance
“…In contrast, search images have been proven to exist in a large range of predators (Tinbergen, 1960;Pietrewicz and Kamil, 1979;Bond, 1983;Melcer and Chiszar, 1989;Allen et al, 1998;Jackson and Li, 2004;Bond and Kamil, 2006). A possible explanation would be that in real systems predators are unable to completely control the prey densities, due to temporal and spatial heterogeneity in the environment, prey variability, multiple predator species etc.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast, search images have been proven to exist in a large range of predators (Tinbergen, 1960;Pietrewicz and Kamil, 1979;Bond, 1983;Melcer and Chiszar, 1989;Allen et al, 1998;Jackson and Li, 2004;Bond and Kamil, 2006). A possible explanation would be that in real systems predators are unable to completely control the prey densities, due to temporal and spatial heterogeneity in the environment, prey variability, multiple predator species etc.…”
Section: Discussionmentioning
confidence: 91%
“…Although the formation of a search image has historically been associated with bird species (Tinbergen, 1960;Pietrewicz and Kamil, 1979;Bond, 1983;Allen et al, 1998;Bond and Kamil, 2006), there is a strong indication that predators from different classes form search images. For example, Jackson and Li (2004) showed that hunting spiders also form search images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. Blough, 1984;Bond, 1983;Pietrewicz & Kamil, 1979). The odd-item method may also be useful in such research, as contrasts between odd-item and other data already suggest.…”
Section: Feature Identificationmentioning
confidence: 99%
“…Hence, the matrix A sets the structural 20 constraints on the food web (e.g., to avoid herbivores to feed on carnivores etc. will call this model the search image model; see also Bond (1983). The second model we use…”
mentioning
confidence: 99%